MicroRNA-223–3p promotes pyroptosis of cardiomyocyte and release of inflammasome factors via downregulating the expression level of SPI1 (PU.1). (30th June 2022) - Zhao, Simin; Tan, Yao; Qin, Jianning; Xu, Haiqiang; Liu, Lingyun; Wan, Hengquan; Zhang, Chi; Fan, Wenjing; Qu, Shunlin
Abstract: Diabetic cardiomyopathy (DCM) is a common heart disease in patients with diabetes mellitus (DM), and is sometimes its main cause of death. Among all the causes of DCM, myocardial cell death is considered to be the most basic pathological change. Furthermore, studies have shown that pyroptosis, the pro-inflammatory programmed cell death, contributes to the progress of DCM. MicroRNAs (miRNAs) also have been proved to take part in the formation of DCM. However, it is not clear whether and how miRNAs regulate myocardial cell pyroptosis in DCM development. In our study, the results showed that the expression of miR-223–3p was significantly increased in cardiomyocytes induced by high glucose, whereas the down-regulation of miR-223–3p weakened it. To understand the signal transduction mechanism of miR-223–3p leading to pyroptosis, we found inhibition of miR-223–3p expression down-regulated caspase-1, pro-inflammatory cytokines IL-1β and other pyroptosis-associated poteins. Moreover, miR-223–3p repressed SPI1 expression. Furthermore, we silenced SPI1 with siRNA to mimic the effect of miR-223–3p, up-regulating the expression of caspase-1 and resulting to pyroptosis. The above findings inspired us to propose a new signaling pathway to regulate scoria of cardiomyocytes under hyperglycemia: miR-223–3p↑→ SPI1↓→ caspase-1↑ → IL-1β and other pyroptosis-associated poteins↑→ pyroptosis↑. In summary, miR-223–3p could be a potential therapeutic target for DCM. Highlight: Diabetic cardiomyopathy(DCM) is a common cardiac condition in patients with diabetes mellitus. Pyroptosis, the pro-inflammatory programmed cell death, contributes to the progress of DCM. MiR-223–3p expression substantially increased in high glucose-induced cardiomyocytes. We unraveled a new pathway composed of miR-223–3p and SPI1 that regulates myocardial pyroptosis.